2017
DOI: 10.1002/pmic.201700180
|View full text |Cite
|
Sign up to set email alerts
|

What is targeted proteomics? A concise revision of targeted acquisition and targeted data analysis in mass spectrometry

Abstract: Targeted proteomics has gained significant popularity in mass spectrometry-based protein quantification as a method to detect proteins of interest with high sensitivity, quantitative accuracy and reproducibility. However, with the emergence of a wide variety of targeted proteomics methods, some of them with high-throughput capabilities, it is easy to overlook the essence of each method and to determine what makes each of them a targeted proteomics method. In this viewpoint, we revisit the main targeted proteom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 52 publications
1
74
0
2
Order By: Relevance
“…On the other hand, PRM is based on Q‐Orbitrap or Q‐TOF as a high‐resolution mass spectrum platform that simultaneously analyzes all fragment ions of a preselected peptide of interest. Differing from SRM/MRM, fragment ion detection is performed by Orbitrap or TOF . Breast cancer‐EV study showed the PRM serves as an essential tool on the initial validation of phosphoproteins .…”
Section: Cancer Ev Proteomics—methods and Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, PRM is based on Q‐Orbitrap or Q‐TOF as a high‐resolution mass spectrum platform that simultaneously analyzes all fragment ions of a preselected peptide of interest. Differing from SRM/MRM, fragment ion detection is performed by Orbitrap or TOF . Breast cancer‐EV study showed the PRM serves as an essential tool on the initial validation of phosphoproteins .…”
Section: Cancer Ev Proteomics—methods and Analysesmentioning
confidence: 99%
“…The selected precursor ion is then fragmented at the second quadrupole (q2) followed by the third quadrupole (Q3) to further detect the fragments (transitions) for protein quantification. [89,90] Stable isotope labeling such as SILAC can be also combined with SRM/MRM analysis to achieve absolute quantification. [91] In cancer EV studies, SRM/MRM is one of the promising strategies to evaluate potential biomarkers using large scale clinical samples.…”
Section: Targeted Ev Proteomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also an emerging third method, called data‐independent acquisition (DIA) or sequential window acquisition of all theoretical fragment‐ion spectra (SWATH‐MS), that combines the advantages of both shotgun and targeted proteomics. In this method, MS/MS data are acquired for all the peptides, while data analysis can be performed in a targeted manner postacquisition by extracting the information of the required peptide . However, for targeted proteomics to reach benchside and bedside, enormous effort is required from the research community, health policymakers, and vendors to produce the infrastructure and expertise at all levels in a cost‐ and user‐friendly manner.…”
Section: From Shotgun To Targeted Proteomicsmentioning
confidence: 99%
“…In this method, MS/MS data are acquired for all the peptides, while data analysis can be performed in a targeted manner postacquisition by extracting the information of the required peptide. [21][22][23] However, for targeted proteomics to reach benchside and bedside, enormous effort is required from the research community, health policymakers, and vendors to produce the infrastructure and expertise at all levels in a cost-and user-friendly manner. This would remove bottlenecks and result in the translational success of proteomics research.…”
Section: From Shotgun To Targeted Proteomicsmentioning
confidence: 99%